PRODUKTIVITAS PEKERJA PADA PEKERJAAN PASANGAN BATA MERAH DI PT. KARYA SEHATI UTAMA PADA PROYEK PERUMAHAN THE JALIMBAR RESIDENCE - , GHULAM AHMAD ROBBANI; , Agus Nugroho, ST ., MT, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : National development goals to be achieved by the nation of Indonesia is building a whole Indonesian people, both materially and spiritually. Productivity is the ability of workers to produce goods or services within a certain time unit. Factors affecting the productivity of workers, among others, experience, salary, discipline, age, distance to force workers to mix and distance plots treated with warehouse material. Purpose : The purpose of this study was to determine the effect size of the variables age, work experience and education level of the level of labor productivity in the installation of red brick in a certain time unit in The Jalimbar Recidence. Research methods : The method used in this research is descriptive analysis method is the study by collecting primary grade and secondary grade. This grade obtained by examining 30 workers doing the masonry work. The tools used include: the form of interviews and observations, digital camera, computer, stopwatch, and stationery. The results : The results of this study showed an average productivity of workers is 0.073 m2/minutes = 4.38 m2/hours = 21,90 m2/day. Average productivity level of the highest obtained by the uneducated 0.081 m2/minutes = 24,30 m2/day. Conclusions : Average productivity can showed by workers is 0.073 m2/minutes = 4.38 m2/hours = 21,90 m2/day. Education level did not significantly affect the resulting level of productivity. Age factor and work experience can affect the resulting level of productivity.